1987
DOI: 10.1088/0031-9155/32/9/009
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of the flash associated with laser-induced plasma in the eye

Abstract: A bright flash of light is emitted by the plasma formed at the focus of an ophthalmic Nd: YAG laser. The purpose of this investigation is to determine whether the plasma flash constitutes a hazard to the operator. The intensity of the flash at the slit lamp eyepiece was measured and the experimentally derived value was verified by independent calculation. For hazard assessment purposes, the concept of a spectrally weighted maximum permissible exposure (MPE) is described in the paper. Based on the MPE and our m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
2
3
0
1
Order By: Relevance
“…The lack of abnormality in the fluorescein angiography indicates that the lesion was not caused by direct action of the laser but, probably, by the laser induced plasma flash (8) . A similar case has been reported by Yang et al (9) , as in Yang's report, the injury observed seems to be caused by radiation emitted by the plasma (10) . However, unlike in Yang's case, in our case the patient was wearing protective goggles and the lesion was less severe.…”
Section: Discussionsupporting
confidence: 86%
“…The lack of abnormality in the fluorescein angiography indicates that the lesion was not caused by direct action of the laser but, probably, by the laser induced plasma flash (8) . A similar case has been reported by Yang et al (9) , as in Yang's report, the injury observed seems to be caused by radiation emitted by the plasma (10) . However, unlike in Yang's case, in our case the patient was wearing protective goggles and the lesion was less severe.…”
Section: Discussionsupporting
confidence: 86%
“…2 The formation of plasma created by tightly focusing of femtosecond laser beams generally presents as a bright flash of blue-white light and emits light radiation harmful to retinal structures. 4 Similar to our previous case, prolonged light exposure, a short distance to the plasma source as well as disuse of protective goggles are the three main factors that contribute to the macular damage in this case series. However, unlike the monocular retinal injury in our past report, both eyes were affected in all three patients in this case series.…”
Section: Discussionsupporting
confidence: 85%
“…2 It has been demonstrated that viewing the plasma flash in a patient's eye through the microscope in clinical practice would not be considered hazardous to the operator. 4 However, during technical procedures, prolonged viewing of a laser-induced plasma flash formed in the air can result in photic retinopathy, as described in the present case series. In this situation, eye protection including a neutral filter adequate to reduce glare as well as the conventional laser eye protection specified at the laser wavelength is recommended.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…6 E tal como neste, a lesão parece ter sido causada pela radiação emitida pelo plasma. 7 Acreditamos que um mecanismo fotoquímico semelhante a uma queimadura solar possa ter causado a lesão. Como acontece nas queimaduras solares, não se observam alterações na angiografia.…”
Section: Discussionunclassified